2014
DOI: 10.1016/j.pneurobio.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced hyperalgesia

Abstract: The importance of the modulation of pain by emotion is now widely recognised. In particular, stress and anxiety, depending on their nature, duration and intensity, can exert potent, but complex, modulatory influences typified by either a reduction or exacerbation of the pain state. Exposure to either acute or chronic stress can increase pain responding under experimental conditions and exacerbate clinical pain disorders. There is evidence that exposure to chronic or repeated stress can produce maladaptive neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
190
2
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(212 citation statements)
references
References 214 publications
7
190
2
13
Order By: Relevance
“…Exposure to chronic stress is more likely to result in stress-induced hyperalgesia or allodynia [561,562], possibly by inducing hypocortisolism that allows upregulation of pro-inflammatory cytokines, which then can sensitize nociceptors. Indeed, there are experimental human data suggesting that cortisol levels are causally involved in modulating pain sensitivity [563,564].…”
Section: Stress and The Stress Response Systems In Fmsmentioning
confidence: 99%
“…Exposure to chronic stress is more likely to result in stress-induced hyperalgesia or allodynia [561,562], possibly by inducing hypocortisolism that allows upregulation of pro-inflammatory cytokines, which then can sensitize nociceptors. Indeed, there are experimental human data suggesting that cortisol levels are causally involved in modulating pain sensitivity [563,564].…”
Section: Stress and The Stress Response Systems In Fmsmentioning
confidence: 99%
“…Many studies have shown the positive correlation between preoperative anxiety and postoperative pain intensity as well as analgesic consumption [5][6][7][8][9]. The phenomenon that exposure to physical or psychological stressors can enhance nociception and pain sensitivity is described as stress-induced hyperalgesia (SIH) [10][11][12][13][14][15][16]. Although more and more attention has been paid to investigate this phenomenon, the potential underlying molecular mechanism has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Migraine patients do not have any obvious injury (although inflammation may be present (41)), but perhaps more relevant is the proposal that chronic stress is a contributing factor to migraine (42). Extensive experimental preclinical studies of chronic stress have shown decreased pain thresholds or increased responses to painful stimuli in many models (40). Further, chronic stress in rats can change β-adrenergic receptor signaling rendering stimulation with epinephrine pro-nociceptive (43), and chronic stress induces visceral hypersensitivity that is attenuated in the presence of beta-blockers (30).…”
Section: Discussionmentioning
confidence: 99%